2016
DOI: 10.12820/rbafs.v.21n5p461-469
|View full text |Cite
|
Sign up to set email alerts
|

Users’ perception of actions, improvement in quality of life and satisfaction with the Academia da Cidade Program

Abstract: The purpose of this study was to analyze the perception of the users of the Academia da Cidade Program in Recife, Northeastern Brazil, regarding their satisfaction with the provision of services and perception of changes linked to quality of life after joining this program. Therefore, a case study with a qualitative approach was performed. The study subjects were 28 users aged between 28 and 73 years, selected intentionally, using the criterion of saturation and diversity of centers. Data collection was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 16 publications
1
31
0
6
Order By: Relevance
“…The studies classified as type I focused on reporting the effects of physical activity sessions offered by the ACP-Recife in the quality of life of participants 11,12 and risk factors associated to hypertension in ACP participants 13 .In addition, the type II studies reported how the Academia da Cidade Program relates to healthy lifestyles 10 , effects in the physical activity levels of the population exposed to the ACP 16 , satisfaction and exposure to the ACP 14 , adhesion of ACP participants 15 and program perception of professionals in the ACP 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies classified as type I focused on reporting the effects of physical activity sessions offered by the ACP-Recife in the quality of life of participants 11,12 and risk factors associated to hypertension in ACP participants 13 .In addition, the type II studies reported how the Academia da Cidade Program relates to healthy lifestyles 10 , effects in the physical activity levels of the population exposed to the ACP 16 , satisfaction and exposure to the ACP 14 , adhesion of ACP participants 15 and program perception of professionals in the ACP 28 .…”
Section: Resultsmentioning
confidence: 99%
“…From that perspective, the Academia da Cidade Program (ACP), linked to the Health Secretariat of Recife since 2002, works as a component of health policy aiming at Primary Care and its goal is to promote physical activity, healthy diet, and health education 9 , where the ACP actions are developed in a system within public open spaces such as parks and plazas 10 . The body of literature on the ACP in Recife is focused in studies on: quality of life, lifestyle, and participant satisfaction [11][12][13] , evaluation of ACP activities 14 , adherence and adhesion of participants 10,15 , effects on the interventions of the ACP in Recife 16 and articulation between the family health units and the ACP 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Ao considerar que ambas podem ser fatores de proteção de doenças crônicas, elas se tornam importantes para a manutenção de hábitos saudáveis (MACIEL et al, 2019;MEIRELES;FERREIRA, 2018;DIETTRICH;PEDRO, 2015;CAMPOS et al, 2014). Ademais, níveis satisfatórios de AF e AS são descritos em outros estudos como um diferencial na percepção da QV, especialmente por contribuir diretamente na capacidade funcional, aspectos físicos, dor e saúde geral (FEITOSA et al, 2016;DIETTRICH;PEDRO, 2015;GONÇALVES et al, 2019). De acordo com os participantes, o VAMOS proporcionou mudanças em outros aspectos, como, por exemplo, na autoestima e socialização dos participantes.…”
unclassified
“…Essas mudanças podem estar vinculadas ao formato dos encontros (dialogado) -rodas de conversas, contribuindo, possivelmente, para a melhora da QV. Uma avaliação realizada em unidades similares a do PAS mostrou que a interação social está relacionada a uma melhora na percepção da QV de participantes de programas comunitários (FEITOSA et al, 2016).…”
unclassified
See 1 more Smart Citation